Immune cell trafficking: a novel perspective on the gut-skin axis - Jiayan Zhang; Zhirong Yao (BMC, 2024)
Abstract Immune cell trafficking, an essential mechanism for maintaining immunological homeostasis and mounting effective responses to infections, operates under a stringent regulatory framework. Recent advances have shed light on the perturbation of cell migration patterns, highlighting how such disturbances can propagate inflammatory diseases from their origin to distal organs. This review collates and discusses current evidence that demonstrates atypical communication between the gut and skin, which are conventionally viewed as distinct immunological spheres, in the milieu of inflammation. We focus on the aberrant, reciprocal translocation of immune cells along the gut-skin axis as a pivotal factor linking intestinal and dermatological inflammatory conditions. Recognizing that the translation of these findings into clinical practices is nascent, we suggest that therapeutic strategies aimed at modulating the axis may offer substantial benefits in mitigating the widespread impact of inflammatory diseases.